COVID-19 Pandemic and Dental Practice - Anuraj Singh Kochhar; Ritasha Bhasin; Gulsheen Kaur Kochhar; Himanshu Dadlani (International Journal of Dentistry, 2020)
SARS-CoV-2, a virus causing severe acute respiratory syndrome, has inundated the whole world, generating global health concerns. There is a wildfire-like effect, despite the extensive range of efforts exercised by the affected countries to restrain the expanse of this pandemic, owing to its community spread pattern. Dental specialists in the upcoming days will likely come across patients with presumed or confirmed COVID-19 and will have to ensure stringent infection prevention and control to prevent its nosocomial spread. This paper strives to provide a brief overview of the etiology, incubation, symptoms, and transmission paradigms of this novel infection and how to minimize the spread in a dental healthcare setting. This review presents evidence-based patient management practice and protocols from the available literature to help formulate a contingency plan with recommendations, for the dental practices prior to patients’ visit, during in-office dental treatment, and post-treatment, during the pandemic and after.